Patient-relevant outcomes following first revision total knee arthroplasty, by diagnosis - Sabah, SA; Knight, R; Alvand, A; Palmer, AJR; Middleton, R; Abram, SGF; Hopewell, S; Petrou, S; Beard, DJ; Price, AJ (Lippincott, Williams & Wilkins, 2023)
Background: The purpose of this study was to investigate patient-relevant outcomes following first revision total knee arthroplasties (rTKAs) performed for different indications.